Analisis Pengadaan Benih Padi Unggul Inpari 32 Dengan Sistem Kemitraan Kelompok Tani Didesa Cinta Damai Kec. Percut Sei Tuan Kab. Deli Serdang (Studi Kasus: UD Damai Tani) - Dicky Oloan Manullang; Mitra Musika Lubis; Muhammad Fadly Abdina (Mahesa Research Institute, 2024)
This study aims to: (1) To find out the Inpari 32 Superior Rice Seed Procurement System at UD. Damai Tani (2) To find out about UD's partnership. Damai Tani with Farmer Groups (3) To find out the income of rice farmers and owners at UD. Peasant Peace. This research was conducted in Percut Sei Tuan District, Deli Serdang Regency, which was determined purposively. The sampling method was carried out using the Proportional Random Sampling method with 39 respondents. The results of the study revealed that the average income of inpari 32 s rice breeders in Percut Sei Tuan District, Deli Serdang Regency, was IDR 6,164.42 per planting season and the income of UD Damai Tani owners was IDR 45,406,000 from the rice price agreed upon by farmers. Paddy with Owner UD. Damai Tani, namely Rp. 200 from the market price and production received by the owner of UD. Damai Tani is only 5,000 kg/ha. However, rice farmers can sell the rest of their production to middlemen at a much higher price.